2002
DOI: 10.1002/nau.10091
|View full text |Cite
|
Sign up to set email alerts
|

Video urodynamics using transrectal ultrasonography for lower urinary tract symptoms in women

Abstract: The symptoms of women with lower urinary tract disorders were frequently accompanied by urethral and/or pelvic floor abnormalities during voiding that were clearly detected by VU-TRUS. VU-TRUS is useful for objective evaluation of female lower urinary tract symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Interpretation of acquired 2D images is also operator dependent. [3][4][5] On the contrary, visualization of 3D structures will facilitate a better understanding of the concerned anatomy because this multiplanar technology allows visualization of the dynamic 3D shapes of the bladder motion during voiding, simultaneously visualized in the axial, coronal, and sagittal planes in the same display. 5 Selection of any sections of the axial, coronal, and sagittal planes is available for demonstration through the acquired 3D volume data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interpretation of acquired 2D images is also operator dependent. [3][4][5] On the contrary, visualization of 3D structures will facilitate a better understanding of the concerned anatomy because this multiplanar technology allows visualization of the dynamic 3D shapes of the bladder motion during voiding, simultaneously visualized in the axial, coronal, and sagittal planes in the same display. 5 Selection of any sections of the axial, coronal, and sagittal planes is available for demonstration through the acquired 3D volume data.…”
Section: Discussionmentioning
confidence: 99%
“…4 Furthermore, the conventional imaging modality of videourodynamic studies can show only 2D images and has not shown the dynamic changes in 3D bladder shape. [1][2][3][4][5] To our knowledge, no previous study showed that dynamic analysis of bladder shape motion was feasible and could be a novel imaging modality for assessment of voiding function and pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through retrospective analysis of VUDS results, Jiang et al [83] discovered that bladder dysfunction usually occurred in male patients over 70 years old rather than BOO, which indicates the effect of VUDS in precise diagnosis and treatment of LUTS. Tosaka et al [84] obtained clear detection results of urethral and pelvic floor abnormalities in LUTS patients by transrectal ultrasonography, proving the effectiveness of VUDS in clinic use. In addition to the above, VUDS is also an important means to improve the skills of the clinicians, [85] playing an important role in this digital era.…”
Section: Video Urodynamics Studiesmentioning
confidence: 96%
“…Tosaka et al. [ 84 ] obtained clear detection results of urethral and pelvic floor abnormalities in LUTS patients by transrectal ultrasonography, proving the effectiveness of VUDS in clinic use. In addition to the above, VUDS is also an important means to improve the skills of the clinicians, [ 85 ] playing an important role in this digital era.…”
Section: Diagnosis and Evaluation Of Lutsmentioning
confidence: 99%